Intersectoral interaction as a mechanism for implementing multilevel governance at the subnational level in transformational conditions - Suvorov, Valentin (Theory and Practice of Public Administration, 2025)
The article examines the essence and features of intersectoral interaction as a mechanism for implementing the concept of multilevel governance at the subnational level.It is found that intersectoral interaction in Ukraine, as a mechanism for multilevel governance at the subnational level, is a key factor in effective management of regional development in the context of decentralization under transformational conditions, as it demonstrates the potential for increasing the efficiency of management based on tripartite cooperation and partnership of various entities, but requires the introduction of effective mechanisms for further improvement, in particular by adapting the best governance practices.It is substantiated that the implementation of the concept of multilevel governance in Ukraine at the subnational level should involve the establishment of intersectoral interaction, which is based on the cooperation of three sectors, which represent local public authorities, a proactive and informed public (non-profit sector), as well as socially responsible entrepreneurship (profit sector). At the same time, the development of intersectoral interaction processes of the above sectors requires further institutionalization and appropriate regulatory and legal regulation.It is specified that the institutional mechanism of intersectoral interaction at the subnational level provides for the development and approval of a number of regulatory documents that provide specification of the content, forms, and effective instruments of such interaction, contribute to the development of various types of cooperation in relation to clearly defined development sectors, and also presupposes the search and implementation of effective organizational measures and control over the adoption and implementation of relevant decisions.It is proved that modeling of intersectoral interaction should be based on the use of a project approach, other management concepts and approaches focused on results, which provides for the specification of the directions and features of such cooperation, the establishment of relationships between the main system-forming components, control points in achieving the results of joint activities, as well as areas of responsibility of interaction entities under transformational conditions.